التواصلية في اعمال الخزاف الاوربي المعاصر ماغنوس غون (مجلة جامعة بابل للعلوم الانسانية, 2017)
Abstract Any plastic artwork is a visual language by itself, it is a mean of communication used by the spectator to understand the artist's style and intends, considering that the finished artwork is a pre-atheistic vision of its presence in the artist's self and his emotions with visual texts of previous configurations. So, the artist still seeks to discover the renewed and modern outputs that meet the society taste such as deleting or adding and inserting new materials to learn about the points of convergence of desires between him and the spectator. These outputs are considered the ground for their relationship which justifies the emergence of the artwork to reflect that composition in a special way that distinguishes it from others through the aesthetic values achieved by the spectator's reading of the language of that work .  It was therefore necessary to recognize the nature of the communicative process that creates a dialogue between the contemporary and previous product, which is a reference basis, to monitor the products, styles and findings of the potter "Magnus Gjoen" and highlights his works "the current study model" directly.The problem of the this research is identified by the following question:Do the works of the potter "Magnus Gjoen" have communicative data?The current study aims to: recognize the communication in the products of the modern European potter "Magnus Gjoen" in his finished works from 2012 to 2016.In order to support the research conceptually, a theoretical framework was created to cover the cognitive aspect to deal with:Communication in the cognitive thought;Modern pottery configuration.The research procedures form the research community which contains 15 works. Its sample includes 5 models which are analyzed according to the descriptive approach followed in this study to learn about the communication in Gjoen's works. The fourth chapter contains the results of this study which are:Communication in Gjoen's works is achieved according to the effectiveness of the formal structures with used metaphors as in all the sample models.Through reading his works, we recognize that there is an effective communicative mechanism in terms of the way of glazing and printing of forms with indications, which is a distinctive icon of previous references as in models 2, 3, 4, and 5.Gjoen exercises an act of associate in his works through borrowing weapons, animals and parts of the human body and treating them by printing to make the maximum conceptual impact by mixing opposing forces in a unique way, such as mixing beauty with destruction and horror and mixing life with death, as he described his works in the sample models.The most important conclusions are:The communication in Gjoen's works is achieved on both formal and technical levels through depending on the fragments of the past as it depends on history and inspiration at the same time.Finally the research is ended with recommendations, suggestions and resources.